Urbanismo entre pares: cidade e tecnopolítica - Ana Isabel Junho Anastasia de Sa (2015)
Nowadays, the growing expansion of digital communication technologies is integrated with the experience and infrastructure of contemporary cities as elements inseparable from their physical-territorial dimension, transforming the ways in which space is perceived, modified and presented. The contamination of human sociability by communication networks manifest itself, however, in a highly controversial way since the same extended connectivity conditions mobilize both the main control and domination mechanisms, as well as potent devices for citizen articulation, intellectual cooperation and collective intelligence. Metropolises not only are impacted by these processes, but, far beyond that, they constitute the paradigmatic territory for such imprecated field of tensions. They are, at the same time, the site for human exchange, encounter and common production, as well as the stage for its expropriation and forceful instrument for social segregation. In this context, new mechanisms for intervention, appropriation and interaction with the urban environment emerge, based on the premises of shared practices and enhancing derisory processes. Such initiatives have been characterized by terms such as peer to peer urbanism, open source city or copyleft city, among others, in direct reference to the informational universe, as well as in opposition to traditional urban planning procedures.These proposals are the subject of this research, which regards communication networks not with the intention of answering just how cities can be transformed by available high tech innovations. It is proposed, instead, to think about how to guide the development of such tools in search of more democratic urban practices.